'Have you ever been to England? You know, they speak really weird English there'. Some implications of the growth of English as a global language for the teaching of English in the UK. (25th February 2013) - Goddard, Angela; Henry, Alastair; Mondor, Monika; van der, Manon
Abstract This article describes two inter‐related research projects concerned with the teaching and learning of English in contemporary contexts, where English is changing its status from being the first language of specific groups of speakers to becoming a global lingua franca. Focussing respectively on learners of English as a second language (L2 users) in the Netherlands and Sweden, and on native speakers (L1 users) in the UK, our research reveals what English as a lingua franca means to some of its European users, and considers ways for L1 teachers and learners to remain connected internationally.